Genre Analysis of University Brochures: A Comparison Between UISU and UMSU Using the MOVE and STEP Model - Arina Putri; Naila, Aisya Naifa; Fransisca, Amanda; Ulfa, Maryam; Margaret, Carissa; Zein, Thyrhaya (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2024)
This study analyzes the promotional brochures of two universities, Universitas Islam Sumatera Utara (UISU) and Universitas Muhammadiyah Sumatera Utara (UMSU), using Askehave and Nielson's (2005) framework for move analysis. The framework identifies nine moves, including attracting attention, greeting, identifying the sender, detailing content, and establishing contact, among others. The analysis reveals both similarities and differences in how these institutions present themselves to prospective students. Both brochures use visually appealing designs, structured layouts, and detailed content to engage readers and emphasize institutional credibility. UISU’s brochure prioritizes practical details, such as scholarships, facilities, and operational transparency, aiming to provide prospective students with comprehensive and actionable information. Conversely, UMSU’s brochure emphasizes its